The institutional and cultural framing of the educational stratification in fertility. A review of the role of labor market institutions and attitudinal orientations. (April 2020) - Bellani, Daniela
Highlights: The share of part time and public sector jobs as well as the strictness of EPL do not modify female educational gradient of fertility. Where postmodernism is widespread, low educated women are less likely to have children than in more traditional societies. A high diffusion of gender egalitarianism is associated with a reduction of the educational gradient. Abstract: The aim of this article is to overcome the incomplete explanation of previous research findings on the societal determinants of the educational fertility differentials in Europe. Our analysis draws on two overlooked factors, the role of labour market setting and the diffusion of new values. Combining ESS, EVS and WVS data for 2004–2009 with contextual indicators on labour market setting and cultural orientations, our multilevel analysis shows that labour market conditions in terms of share of part time jobs, dimension of public sector employment and strictness of EPL do not systematically modify the gradient of fertility by parities. But instead, we observe a clear moderator effect of attitudinal orientations. Results show that in societies where postmodernism is widespread, both high and low educated women are less likely to have children. A high diffusion of gender egalitarianism is associated with a reduction of the gradient through an increase of the likelihood of having a child especially for higher educated women. This article concludes by highlighting some responses to societal polarization of fertility related to both structural and cultural factors and indicates avenues for future research on the social stratification of fertility.